IN SEARCH OF “ITS OWN LAND.”THE RULE OF LAW AND SECURITY IN THE CAUCASUS - MARKEDONOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2004)
Security” is a word equally applied to private lives and society as a whole. Thomas de Waal, Cau-casus Editor for the London Institute for War and Peace Reporting (IWPR), is convinced that in the Caucasus individuals and societies are no longer secure.1 One tends to agree with him: the words “the Caucasus and conflicts,” “the Caucasus and war,” “the Caucasus and refugees” were paired at the last stage of Soviet history and remain paired at the early stages of post-Soviet developments. On the eve of the Soviet Union’s disintegration the region lost its stability, today it is emanating instability that threatens not only Russia and the new South Caucasian states. In fact, the EU members are looking at it as a source of threat, too. The steadily increasing outflow of migrants from the North Caucasian republics that are part of the Russian Federation and from the South Caucasian countries (the same happened ear-lier when people were leaving the zone of the Balkan conflict en masse) forces Europe to look deeper into the processes unfolding in one of the most unstable post-Soviet areas. They can no longer be regarded as something external in relation to Europe—they have already developed into an internal political factor.he United States as the main antiterrorist fighter is fully aware of the Caucasus as a potential source of new terrorist acts that might affect America’s national interests. Even if Russia, the EU and the United States do not agree on the sources and causes of crises and conflicts in the Northern and Southern Caucasus and on the methods of their settlement, they all agree that sustainable economic development, large investments, partnership and a complete integration of the Caucasian powers (Russia, Georgia, Armenia and Azerbaijan) into the world community will remain impossible unless the armed and “frozen” (so far) as well as latent ethnic conflicts on their terri-tories are finally settled. I have included Russia among the Caucasian states deliberately; by doing this I do not aim at saying that Russia has any political claims to a “special mission” in the region and to the neo-imperial status. In fact, Russia’s North Caucasian possessions are twice as large as the independent South Caucasian states taken together. Russia’s role is not limited to geographical considerations.The Caucasian region delineated by the lower reaches of the Don and the Volga in the north and by the southern borders of three South Caucasian republics in the south (this is stated with a great degree of conventionality) is a most complicated conglomerate of varied languages, anthropological types, religions, social and political traditions that are tearing it apart. At the same time, the past abounds in common and shared features that make it possible to describe the region as a cultural-historical, or even civilizational, entity.